Investigation of Association between Susceptibility to Leprosy and SNPs inside and near the BCHE Gene of Butyrylcholinesterase - Henrique J. P. Gomes; Ricardo L. R. Souza; Flávia Costa Prevedello; Marcelo Távora Mira; Eleidi A. Chautard-Freire-Maia (Journal of Tropical Medicine)
Leprosy is a chronic disease caused by Mycobacterium leprae and affects the skin and the peripheral nervous system. Butyrylcholinesterase is coded by the BCHE gene, and the atypical allele (70G; rs1799807) has been investigated as a leprosy risk factor, with conflicting results. The present study estimated the frequencies of variants of rs1799807 and of five additional SNPs at the BCHE gene or near it: rs1126680, rs1803274, rs2863381, rs4440084, and rs4387996. A total of 167 patients and 150 healthy controls were genotyped by TaqMan PCR. Significantly higher allelic (70G) and genotypic (70DG) frequencies in rs1799807 were found in the patient group, with odds ratio (OR) of 6.33 (1.40 to 28.53) for the heterozygote. This finding was replicated in a comparison of the cases against a control group of 361 blood donors. The present data suggest that the atypical BChE variant may predispose to leprosy per se.